2002
DOI: 10.1007/s11661-002-0211-5
|View full text |Cite
|
Sign up to set email alerts
|

Hot rolling texture development in CMnCrSi dual-phase steels

Abstract: The amount of strain below the temperature of nonrecrystallization, T nr , has an important influence on the phase fractions and the final crystallographic texture of a hot-rolled dual-phase ferrite ϩ martensite CMnCrSi steel. The final texture is influenced by three main microstructural processes: the recrystallization of the austenite, the austenite deformation, and the austenite-to-ferrite transformation. The amount of strain below T nr plays a major role in the relative amounts of deformed and recrystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…The ferrite b-fibre is the transformation product from the austenite b-fibre, which represents the characteristic texture components of the deformed FCC material with high stacking fault energy (SFE). 15,16) A rotated cube recrystallization texture component {001}͗110͘ is also presented in the ODF with the intensity of 2ϫ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ferrite b-fibre is the transformation product from the austenite b-fibre, which represents the characteristic texture components of the deformed FCC material with high stacking fault energy (SFE). 15,16) A rotated cube recrystallization texture component {001}͗110͘ is also presented in the ODF with the intensity of 2ϫ.…”
Section: Resultsmentioning
confidence: 99%
“…10(d)). According to some authors 2,13,15) these texture components could emerge from either deformed or recrystallized austenite (see Fig. 9(b)), but the later is less probable, taking into account the Nb content of steel B, the rolling parameters and the model predictions.…”
Section: Texturementioning
confidence: 97%
“…el esfuerzo de fluencia y el esfuerzo tensil máximo y la ausencia de fluencia heterogénea. En general estos resultados se encuentran en el rango de los aceros HSLA [8] .…”
Section: Caracterización Mecánicaunclassified
“…Recently, the degradation of ductility and impact toughness of DP steels has been receiving attention and this phenomenon has been attributed to the formation of coarse martensite phases as the intercritical annealing temperature increases [3,5,6]. It has been shown that the ductility and fracture toughness can satisfactorily be optimized by developing microstructures with fine distribution of ferrite and martensite in DP steel either by introducing new alloy design or adopting an appropriate heat treatment procedure [3,6,7]. On the basis of alloying design, the new chemistries are low in carbon and rich in hardenability enhancing element such as…”
Section: Introductionmentioning
confidence: 99%